ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LEVERAGE DENGAN DPR SEBAGAI MEDIATOR PENGARUH INSIDER OWNERSHIP DAN SALES GROWTH TERHADAP LEVERAGE - Sudarmanto, Anggito P.; Demi Pengestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2017)
This research aims to analyze the factors that affects leverage which is indicated by total debt to total asset ratio. The object of this research refers to manufacturing companies that are listed on the Indonesia Stock Exchange (IDX) during the period 2011-2015.The population of this study are 142 manufacturing companies that are listed on the Indonesia Stock Exchange (IDX) during 2011-2015. The data are collected from the Bloomberg terminal and with purposive sampling and some criteria, 79 companies are sampled for the object of this study. The data are analyzed by the multiple regression and Sobel test to identify the mediation of the mediator variable.This research founds that size and tangibility positively and significantly affects the company leverage. Profitability, liquidity and dividend policy is negatively and significantly associated with leverage while insider ownership and sales growth insignificantly affects leverage. Insider ownership and sales growth are proven to be significantly negative affecting the dividend policy. Dividend policy are able to mediate sales growth effect on leverage, while unable to mediate the insider ownership effect on leverage.